1988
DOI: 10.1177/0887302x8800700105
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem, Age Identification, and Media Exposure of the Elderly and their Relationship to Fashionability

Abstract: The study examined the relationship between the fashionability of the elderly (65 and older) and its correlates. Dillman's Total Design Method approach was executed to conduct the survey. Four hundred and thirty elderly men and women participated in the study. The data were analyzed using descriptive statistics, factor analysis, and t-tests. The results indicated that significant differences existed between fashionability and media exposure for the female styles. No differences were found between fashionabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
0
19
1
1
Order By: Relevance
“…Similarly, Barak and Stern (1985) noted that fashion-conscious women often feel younger than their chronological age. However, no relationship was found between age perception and fashion consciousness in Chowdhary's (1988) study. She also observed that although 80% of persons aged 65-91 said that they preferred to wear 'stylish clothing'; only 25% actually chose apparel that was currently fashionable.…”
Section: Fashion Consciousnesscontrasting
confidence: 38%
“…Similarly, Barak and Stern (1985) noted that fashion-conscious women often feel younger than their chronological age. However, no relationship was found between age perception and fashion consciousness in Chowdhary's (1988) study. She also observed that although 80% of persons aged 65-91 said that they preferred to wear 'stylish clothing'; only 25% actually chose apparel that was currently fashionable.…”
Section: Fashion Consciousnesscontrasting
confidence: 38%
“…Hogge et al (1988) and Chowdhary (1988) found that elderly men tended to prefer traditional styling. Only about one-third of the men had fitting problems and few required complicated alterations.…”
Section: Discussionmentioning
confidence: 99%
“…They called it ‘age identification’. Chowdhary 18 referred it to as ‘age perception’ in a research study that looked at the correlates of fashionability for older consumers. Age perception was not related to fashionability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liskey‐Fitzwater et al 10 studied clothing interest for another special needs group and reported that clothing interest did not differ among female adolescents with or without scoliosis. Chowdhary 18 reported that apparel significance was positively related to body type. Endomorphic older consumers rated significantly lower on apparel significance than mesomorphic and ectomorphic individuals.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation